PENGARUH KUALITAS LAYANAN, COMPLAINT HANDLING DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN - Mulyanto Mulyanto; Ika Susilowati (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2021)
This study aims to test and analyze how the influence of service quality, compliance handling and corporate image on customer loyalty at PT JNE Cilacap branch. The population in this study were 88 customers at PT JNE Cilacap Branch. The technique of collecting data by distributing questionnaires. The analysis used is the validity test, reliability test, classic assumption test, multiple linear regression analysis test and the coefficient of determination. The data processing tool used is SPSS for windows version 23.0. The results of this study indicate that: (1) Service Quality has a positive and significant effect on Customer Loyalty, (2) Complaint Handling has a negative and insignificant effect on Customer Loyalty, (3) Company image has a negative and insignificant effect on customer loyalty.